Biometric Authentication System Using Palm Vein Features - Jeyakalyani, A; Suguna, N (International Journal of Computer Sciences and Engineering, 2025)
Textual passwords are not uncommon, which are used for authentication as account based passwords. However these passwords are facing risk in the form of phishing attack, burette force attack, social engineering attack and social surfing as well. The thing consisting of authentication, verification and recognition has been known as biometrics, which is being used for human recognition. Biometric passwords replace the techniques of textual passwords and also function as alternatives. Existence of biometric systems is commonly found by using fingerprint, face, iris, etc., on the other hand its risk to duplicating a fake (For e.g.:- “fingerprint gummy finger”). Palm vein authentication is yet another modern biometric technique, which employs the vein pattern in the human palm in order to verify the person’s identity. Palm vein on classical biometric (e.g. fingerprint, iris, face). Which have merits, are a low risk of falsification, difficulty of duplicated and stability. The recent and current method which has been proposed to detect a hand vein by using Near Infrared (NIR) Light method. The Captured vein image is used in an infrared illuminator and Radon feature techniques is used to extract the feature of hand vein and feature matching algorithm is used. This is the system implemented using MATLAB